Systematic Literature Review: Can the Use of the RADEC Learning Model Enhance Students' Critical Thinking Skills? - FH, Yuliana; Amrina, Dian Eka; Firmansyah, Firmansyah (Journal of Economics Education and Entrepreneurship, 2024)
RADEC learning model (read-answer-discuss-explain-create) strives to actively involve students in learning activities because, in the 21st-century era every student is required to have critical thinking skills which must be trained through learning activities that support students to be able to build their knowledge independently. This research aims to analyze various previous research results and development trends in using the RADEC learning model to improve students' critical thinking skills when applied in Microeconomic Theory courses. The research method used is a systematic literature review. Researchers collected 70 articles published in 2020-2024 in accredited scientific journals sourced from the database of Google Scholar related to the topic being studied. The article metadata identification process is carried out using the Mendeley application and analyzed using the application Vosviewer. Based on the systematic literature review that has been carried out, the results show that the RADEC learning model can improve critical thinking skills, communication, and collaboration skills because students are directed to be able to find solutions to the problems being studied. Apart from that, the syntax of this learning model adapts to Vygotski's social constructivism theory, that the process of building knowledge can be carried out through a process of social interaction through various discussion and collaboration activities. This learning model can be applied in multiple fields of study, including microeconomic theory courses which have contextual learning content and are very close to students' lives, so it can be said that the RADEC learning model has great potential in improving students' critical thinking skills in microeconomic theory courses.